The diagnostic accuracy of chest Xray screening for silicosis: a systematic review, meta-analysis and modelling study - Howlett,P; Durairaj,A; Lesosky,M; Feary,J (Occupational and Environmental Medicine, 2026)
Objectives: Chest Xray (CXR) is widely used for silicosis diagnosis, despite concerns egarding sensitivity. We investigated the diagnostic accuracy of CXR for silicosis screening compared to computed tomography (CT), high-resolution CT (HRCT) and autopsy, and modelled the relationship between CXR sensitivity and disease severity. Methods: Medline, Embase, Scopus, and Web of Science databases were searched on 2nd July 2024 (Prospero registration: CRD42024513830). Meta-analyses were performed by reference standard and at increasing reference test severity cut-offs. The Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool assessed risk of bias. In scenarios of fixed and relative sensitivity, according to disease severity, we estimated missed silicosis cases and the number needed to screen (NNS) in hypothetical populations of low (5%), medium (15%) and high (30%) silicosis prevalence. Results: Twenty studies included 2156 participants and 1105 silicosis cases. CXR had moderate sensitivity (0.76; 95% confidence interval (CI): 0.63-0.86, I2=84%) and high specificity (0.89, 95% CI: 0.77-0.95, I2=57%) compared to HRCT in 12 studies, and low sensitivity (0.50, 95% CI: 0.45-0.55, I2=0%) and high specificity (0.91, 95% CI: 0.87-0.93, I2=20%) compared to autopsy in two studies. CXR sensitivity increased with higher reference test severity cut-offs. Clinically relevant numbers of cases were missed in fixed and relative sensitivity scenarios; increased prevalence and less severe disease resulted in more missed cases and a lower NNS.Conclusions: Silicosis severity and reference test type both plausibly influence CXR sensitivity. Assuming either fixed or relative sensitivity results in missed silicosis cases. Judicious HRCT screening is likely to improve case detection.